First Incoherent Scatter Measurements and Adaptive Suppression of Field-Aligned Irregularities by the PANSY Radar at Syowa Station, Antarctic - Hashimoto, Taishi; Saito, Akinori; Nishimura, Koji; Tsutsumi, Masaki; Sato, Kaoru; Sato, Toru (Journal of Atmospheric and Oceanic Technology, 2019)
journal article